Lives in exile: foreign political refugees in early independent Greece (1830–53). (October 2019) - Aliprantis, Christos
Abstract : This article discusses the stay in Greece of Italian and Polish political refugees of the 1830–1 and 1848–9 European revolutions. The article depicts the human geography of the refugees and examines the experience of exile both collectively and individually. Apart from studying the émigré communities as a whole in Athens, Patras and Syros, this paper also analyses the problems and expectations of specific refugees in Greece after 1849 (e.g. Antonio Morandi, Marco Antonio Canini, Oronzio Spinazzolla). This contribution thus adds to our understanding of both Greece under King Otto and the Mediterranean by highlighting aspects of transnational mobility and interaction of peoples and ideas in the mid-nineteenth century.